Implementasi Nilai-Nilai Keagamaan dalam Menguatkan Sikap Moderasi Beragama Melalui PAI di SDIT Mutiara Ilmu Bangkalan - Hanaris, Fitria (Proceedings of Annual Conference for Muslim Scholars, 2024)
This article aims to explore the implementation of religious values in strengthening religious moderation through Islamic Religious Education (PAI) at SDIT Mutiara Ilmu Bangkalan. The method used is a qualitative descriptive approach with case studies. Data was collected through in-depth interviews, participant observation and documentation. The research results show that SDIT Mutiara Ilmu Bangkalan implements learning strategies to strengthen attitudes of religious moderation including direct learning, dialogue, and familiarization with practices that contain elements of religious moderation. The research results also show that students show a good understanding of religious moderation and more tolerant behavior and respect for differences. Based on these findings, it also indicates that Islamic Religious Education not only functions to increase religious knowledge, but also plays an important role in forming moderate and inclusive student attitudes. It is hoped that this research can contribute to the development of Islamic religious education that is more moderate and adaptive to the challenges of a pluralistic society. Keywords: Religious moderation, Islamic Religious Education, Implementation of religious values, Integrated Islamic School, SDIT Mutiara Ilmu Bangkalan.